Ground-penetrating radar from Kingsbury Pond, Maine, USA - Ian M Nesbitt; Seth W Campbell (PANGAEA, 2021)
We collected ground-penetrating radar (GPR) at Kingsbury Pond, Kingsbury Plantation, Maine, USA on three occasions from 2017-2019 in order to attempt to quantify sediment volume and delineate sedimentary structure. Data was collected using a Geophysical Survey Systems Incorporated (GSSI) 100 MHz radar antenna and SIR-3000 and SIR-4000 control units. One dataset (2017-07-25) was collected in the hull of a wooden canoe, both others (2018-03-03 and 2019-03-09) were collected by towing the antenna across lake ice. Data includes radar profiles (DZT format), metadata (DZX format), and location data with 3 m uncertainty (DZG format containing NMEA 0183 strings). File formats are proprietary to GSSI radar systems but can be accessed using free software.